Manajemen Resiko Cloud Computing Pada UMKM - Dwiki Rasya Rahadian; Valentino Yoss Mahendra; Rico Dwi Yuliyanto; Sulistyo; M. Abdullah Sholihin (Prosiding Seminar Nasional Teknologi Informasi dan Bisnis, 2023)
The business world is now starting to compete globally, where the market is very large. Businesses need fast and accurate information to stay ahead of the competition and keep their customers happy. Building an IT infrastructure to manage data requires a lot of capital, which may not be difficult for large companies, but completely impossible for small companies like (MEME) because they don't have enough start-up capital. Cloud services have become a strong topic in information technology in recent years. Cloud services provide a variety of services including various hardware, infrastructure, platforms, and applications. Cloud services have evolved into solutions and services that increase reliability, reduce IT costs, and offer significant opportunities to the IT industry. The purpose of this research is to evaluate the benefits of using cloud services to increase the competitiveness of small and medium enterprises. This method involves studying documents and books and using the Internet to gather information and make observations. This study looks at the use of information technology in SMEs and also explains how cloud technology can be an alternative solution for SMEs to compete with big companies in the global era .